A Nationwide Community Survey of Prevalence of Circumcision among Egyptian Children and Risk of Hepatitis B Viral Infection - Salama, Iman I; Sami, Samia M; Salama, Somaia I; Elmosalami, Dalia M; Saleh, Rehan M; Said, Zeinab N; Shaaban, Fatma A; Abdel Mohsen, Aida M; Rabah, Thanaa Mahmoud; Abdel-Latif, Ghada A; Fouad, Walaa A; Mohsen, Amira (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: To assess prevalence and risk factors of circumcision among Egyptian children and to assess the risk factors for HBV infection among them. METHODS: A nationwide community survey was carried out on 3306 children aged from 9 months to 16 years, of both genders. Data were collected during face to face interviews with the parents and children. All studied children had received HBV vaccination during infancy. Total anti-HBc and HBsAg were assessed by ELISA followed by HBV DNA detection for positive cases by Real-time PCR. RESULTS: Prevalence of circumcision was 92.3% among boys and 29.7% among girls. The percentage of circumcised girls was significantly higher in rural (38.1%) than urban (21.1%), P<0.01 and more in Upper (42.2%) and Lower Egypt (27.6%) compared to Cairo, the Capital (14.1%), P˂0.001. Boys showed significantly higher prevalence of circumcision in urban (94.1%) compared to rural areas (90.1%), P˂ 0.001.The prevalence of HBV breakthrough infection, detected by HBV-DNA, was 14/3306 (0.42%). No significant differences between circumcised and non-circumcised boys and girls regarding the different serological tests of HBV infection, P > 0.05. Using logistic regression analysis, mothers’ illiteracy or having primary and preparatory education carried six times and 2 times risk respectively of having their daughter circumcised compared to higher education, P < 0.01. Living in Upper or Lower Egypt carried three times and 1.5 times risk respectively of having circumcised girl compared to the Capital, P < 0.001. HBV infection among family was the independent risk factor for HBV infection among girls and boys, in addition to frequent medical injection among boys, P < 0.05. CONCLUSION: Circumcision among girls is still a problem especially in Upper Egypt and in rural areas. Child circumcision in Egypt seems not to play a role in HBV infection and intra-familial HBV transmission and frequent medical injection are the most important risk factors.